Application of UPWr_E124 phage cocktail for effective reduction of avian pathogenic Escherichia coli in mice and broiler chickens - Sáez, David (2025)
Avian pathogenic Escherichia coli (APEC) is the main causative agent of colibacillosis, causing poultry respiratory infections, mortality and economic loss. APEC poses a serious threat to public health and food safety due to its multi-drug resistance and capacity to form biofilms. Bacteriophages (phages) have emerged as an alternative to antibiotics. To cure APEC-infected chickens, a cocktail consisting of UPWr_E1, UPWr_E2 and UPWr_E4 APEC-specific phages was developed and tested. In this study, we documented the maintenance of their activity in neutralized simulated gastric fluid (SGF) conditions and the efficiency of the UPWr_E124 phage cocktail in inhibiting APEC in biofilm structures on chicken breast meat surfaces. Further, we evaluated the efficacy of the UPWr_E124 phage cocktail against APEC in vivo in murine and chicken infection models. In experimentally infected mice, we evaluated the intraperitoneal and gastric gavage administrations of phages. The study revealed that gastric administration of phages reduced bacterial levels in the respiratory system. Moreover, we tested the UPWr_E124 phage cocktail in a chicken model of infection, where phages effectively reduced the number of APEC in the lungs, bursa of Fabricius and blood. These results suggest that the UPWr_E124 phage cocktail could be a potential treatment for colibacillosis in the poultry industry. © 2025 The Authors